Pengaruh Ukuran Perusahaan dan Profitabilitas Terhadap Penghindaran Pajak: Peran Komite Audit Sebagai Variabel Moderasi - Indah Permatasari; Heppy Purbasari (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of company size and profitability on tax avoidance with the audit committee as a moderating variable in the banking sector listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. A quantitative approach is used with descriptive and explanatory research types. The sample was determined using a purposive sampling technique with certain criteria, such as the availability of financial reports and the existence of an audit committee. Data were obtained from financial and annual report documentation, then analyzed using descriptive statistics, classical assumption tests, and panel data regression. The results of the study indicate that company size has a positive and significant effect on tax avoidance, while profitability has a negative and significant effect. However, the audit committee does not moderate the relationship between company size and profitability on tax avoidance, but rather acts as a moderating predictor. These findings provide important implications for companies to increase the effective role of the audit committee in overseeing financial strategies.